Labour formalization and declining inequality in Argentina and Brazil in 2000s: A dynamic approach - Maurizio, Roxana del Luján (2014)
This paper analyses the processes of labour formalization in Brazil and Argentina and its interrelation with the evolution of income inequality over the 2000s. It also contributes to the debates on formalising the informal and how to reduce income inequality.